The Grammatical Interpretations in the Udāna Aṭṭhakathā by Ᾱcariya Dhammapāla: A Critical Analysis - Medhacitto, Tri Saputra (Jounal Nyanadassana, 2024)
This research aims to explore the grammatical interpretations found in in the Udāna Aṭṭhakathā, a commentary attributed to Ᾱcariya Dhammapāla. The Udāna Aṭṭhakathā represents a significant work within Theravāda Buddhism. Ᾱcariya Dhammapāla, following the Mahāvihāra tradition, wrote the commentary on Udāna, by giving more information and elucidation of words with grammatical interpretation. Through this library research, this research investigates the methodology utilized by Ᾱcariya Dhammapāla in his commentaries. It highlights his method to follow the traditional grammatical rules while providing an interpretation of the canonical texts. The study draws upon primary and secondary sources to investigate Ᾱcariya Dhammapāla's approach to grammatical interpretation. Pāli literature including canon and commentaries are considered as the primary sources. While, secondary sources represented by books, journals, articles and previous research related to the topic. As results, this research provides deep understanding on the Ᾱcariya Dhammapāla's commentary, his methodology in writing the commentary and the grammatical interpretations in his commentary.